Land Price Mapping in the Northern Suburbs of Bandung City - Somantri, Lili (Forum Geografi, 2020)
The Northern Suburbs of Bandung City are the areas affected by the expansion of Bandung City. In fact, one of the impacts of the expansion is the increase in land prices on the Northern Suburbs of Bandung. This present study aims at mapping the land prices and finding out factors affecting the land prices on the Northern Suburbs of Bandung. The method used in this study was a descriptive approach by explaining the results of the field analysis. The data were collected by interviewing 120 respondents accidentally in all villages bordering Bandung City. The data were analyzed using percentage analysis and spatial modelling. The results showed that the most expensive land price in 2019 could be found in Cimenyan District, specifically located in Ciburial Village at the price of Rp. 3,437,000 per square meters, in Lembang District, particularly in Lembang Village at the price of Rp. 5,000,000 per square meters, and in Parongpong District, particularly in Ciwaruga Village at the price of Rp. 4,312,500 per square meter. The increased land prices in the Northern Suburbs of Bandung City is caused by the ease of accessibility, the establishment of many luxury settlements, and tourism sites.